Caracterização de interfaces para aplicações em ultra-alto vácuo através de brasagem dissimilar entre nitreto de boro hexagonal (h-BN), a liga de adição Ag-Cu-Ti e o Mo metálico - Rosales, Marcio José Cuccolo (2020)
This work aimed to evaluate the vacuum brazing of h-BN/Mo systems for fabrication of the BPM (Beam Position Monitor) in synchrotron radiation beam. The h-BN has low surface wettability and is difficult to weld. The materials used to compose the metal-ceramic joint were Fe-Ni-Co, due to its low coefficient of thermal expansion, metallic molybdenum (Mo) and h-BN, due to its excellent dielectric properties. The formation of the brazing interface depends on the surface wettability of h-BN by the Ag-Cu-4,5-Ti brazing alloy. Brazing was performed at 865 °C, high vacuum atmosphere (10-5 mbar), with a holding time of 5 min. Computational finite element simulation was performed to evaluate thermal stresses in the brazed joint. The microstructural characterization of the brazing interfaces was performed using scanning electron microscopy (SEM) and Localized Ion Beam (FIB). The tightness tests of the brazed BPM were carried out to determine the tightness of the pieces and their application in ultra-high vacuum. The simulation results showed the existence of critical points in the brazed joint due to the BPM geometry, with the formation of residual compressive stresses, originated by the difference between the thermal expansion coefficients of the materials. The microstructural characterization demonstrated the formation of a continuous joint without defects, with formation of new phases and complex compounds. The brazing alloy promoted the reaction between the active metal and the h-BN, forming new phases at the interface, in addition to eutectoid structures inside the remaining alloy. The formation of TiN and TiB2 compounds in a layer adjacent to h-BN was verified. The properties of the brazed component indicated tightness of 3x10-10 mbar to operate in ultra-high vacuum and brittle fracture in the ceramic material, which shows that the mechanical resistance of the brazed joint was superior to that of the base material.